EFEKTIFITAS PENDAMPINGAN CARA MENYIKAT GIGI METODE KOMBINASI TERHADAP SKOR PLAK PADA PENDERITA DISABILITY - Aryani Widayati; Siti Hidayati (Jurnal Kesehatan Gigi, 2017)
TITLETHE EFFECTIVENESS OF ASSISTANT-DESIGNED PROGRAM TO APPLY COMBINATION METHOD OF TOOTH BRUSHING TO PLAQUE SCORE OF DISABILITY PATIENTSABSTRACTDental health problems, the level of oral hygiene has a very important role in maintaining and maintaining dental health and periodontal membrane because dental and mouthdiseases is a prevalent disease of national health problems. The way to maintain cleanliness is to brush your teeth properly and correctly, not to the exception of people with visual impairment or visually impaired because there are limitations so to teach how to maintain oral hygiene is required assistance. Purpose of research to know the difference of toothbrushing with plaque score in blind at SLB A Yaketunis Yogyakarta.The research used a quasi experiment. The study was conducted in SLB A Yaketunis Yogyakarta with total sampling technique as many as 40 respondents. Data about plaque score is known through index dental examination by PHP, before and after plaque score treatment is known by measuring the level of oral hygiene and measurement (scoring). Normality test data by the Saphiro-Wilk. The results of the normality of the data showed p 0,05, which means that the data are normally distributed. The data obtained were analyzed using statistical t-test.The results used statistical test t-test showed p value 0,000 0,05, according to the basis of decision making can be concluded as Ho rejected and Ha accepted, which indicate there are different scores of plaque before and after being treated on respondents.